2014
DOI: 10.3389/fpls.2014.00495
|View full text |Cite
|
Sign up to set email alerts
|

Hypocotyl adventitious root organogenesis differs from lateral root development

Abstract: Wound-induced adventitious root (AR) formation is a requirement for plant survival upon root damage inflicted by pathogen attack, but also during the regeneration of plant stem cuttings for clonal propagation of elite plant varieties. Yet, adventitious rooting also takes place without wounding. This happens for example in etiolated Arabidopsis thaliana hypocotyls, in which AR initiate upon de-etiolation or in tomato seedlings, in which AR initiate upon flooding or high water availability. In the hypocotyl AR o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 226 publications
1
83
0
1
Order By: Relevance
“…On the other hand, ethylene inhibits auxin-stimulated adventitious root formation. It must be noted that, in other species, ethylene can stimulate adventitious root formation and that other hormones are also involved in the formation of adventitious roots (for review, see Bellini et al, 2014;Verstraeten et al, 2014).…”
Section: Ethylene and Adventitious Root Developmentmentioning
confidence: 99%
“…On the other hand, ethylene inhibits auxin-stimulated adventitious root formation. It must be noted that, in other species, ethylene can stimulate adventitious root formation and that other hormones are also involved in the formation of adventitious roots (for review, see Bellini et al, 2014;Verstraeten et al, 2014).…”
Section: Ethylene and Adventitious Root Developmentmentioning
confidence: 99%
“…We do not know when during the maturation process, the ectopic embryos on mature somatic embryos of Norway spruce are initiated, but they differentiate just below the cotyledons and seem to originate from cells neighboring provascular tissues. It has been shown that pericycle cells in the hypocotyl of both angiosperms (reviewed in Verstraeten et al 2014) and gymnosperms (Grönroos and von Arnold 1988) have the potential to differentiate adventitious roots.…”
Section: Overexpression Of Pahap3a During Embryo Maturation Stimulatementioning
confidence: 99%
“…Since then, it has been well established that ethylene has a positive effect on AR development and emergence (Drew et al 1979 ;Verstraeten et al 2014 ). Since then, it has been well established that ethylene has a positive effect on AR development and emergence (Drew et al 1979 ;Verstraeten et al 2014 ).…”
Section: Roles Of Phytohormones In Adventitious Root Formationmentioning
confidence: 99%